Peran Kepala Sekolah sebagai Manager dalam Mewujudkan Anti Bullying - Nurhayati, Dwi; Abdullah, Ghufron; Ginting, Rosalina Br. (PGRI Kota Semarang, 2024)
The focus of this research is (1) The role of the school principal in planning the anti-bullying program at Aisyiyah Bustanul Athfal 01 Kejiwaan Kindergarten. (2) The role of the school principal in organizing an anti-bullying program at Aisyiyah Bustanul Athfal 01 Kejiwaan Kindergarten. (3) The role of the school principal in implementing the anti-bullying program at Aisyiyah Bustanul Athfal 01 Kejiwaan Kindergarten. (4) The role of the school principal in supervising the anti-bullying program at Aisyiyah Bustanul Athfal 01 Kejiwaan Kindergarten. This research uses qualitative research with a descriptive analytical approach. This research intends to explore the role of the principal as a manager in realizing anti-bullying in Aisyiyah Bustanul Athfal 01 Kindergarten. Data collection techniques in this research used interviews, observation and documentation. Data validity using triangulation. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. Research results a) Analysis of the role of school principals in planning anti-bullying programs is (1) analyzing and identifying child delinquency problems, (2) analyzing the needs of teachers and children, (3) Preparing a draft MOU joint agreement between the school and parents as guardians of students, (4) prepare a budget according to needs for aspects that require financing. b) Analysis of the role of school principals in organizing anti-bullying programs 1) allocating resources; 2) formulate and assign tasks; 3) establish necessary procedures; 4) establish an organizational structure that shows the lines of authority and responsibility. c) Analysis of the role of the school principal in implementing the anti-bullying program including 1) The role as a facilitator by providing image media, posters about the dangers of bullying, 2) The role as a demonstrator of the school principal instructing teachers to be able to clearly demonstrate the dangers and impacts of Bullying, 3) The role as Motivators provide encouragement and direction to children and teachers to live together and help each other, 4) the role as evaluator of the school principal observes children's development with observation sheets and evaluates the dynamics and impact of handlers. d) The role of the school principal in supervising the anti-bullying program includes internal supervision carried out by the principal and supervisor, then external supervision carried out by the school committee, from a technical perspective, supervision is carried out using two approaches, namely direct technical supervision and indirect supervision in the form of reports.